Food, markets, and governance: a new lens on the emergence of collective institutions - Blanton, Richard E.; Feinman, Gary M. (Frontiers in Human Dynamics, 2025)
We employ access to food as an analytical lens to compare and explore the interplay between economic practices and political change in three premodern complex societies: Early Imperial China (primarily the Han Dynasty), the Athenian democracy, and Medieval to Early Modern England. Explicitly framed by the theory of political collective action and economists’ notions of capital and competitive markets, we illustrate how food economies had a key role in shaping the political evolution of collective governing institutions. Although the three cases had divergent historical trajectories, we focus on a persistent and dynamic social process, outcomes of an active discordance between two expressions of economic action, the “capitalist impulse” and the “egalitarian impulse.” In the former, a wealthy elite, enabled by autocratic rulers, strived to realize unearned profits by free riding on the labor of subaltern populations. The egalitarian impulse reflected responses of effected persons to counter such actions through their own agency and by encouraging institution-building that spurred phases of egalitarian political change. Through this comparative processual analysis, we elaborate a key dynamic that spurred past episodes of political transformation while also providing a useful new vantage on current rhetorical arguments concerning the interrelationship between state formation/political institutions and commercial economies.